2022
DOI: 10.3389/fpsyt.2022.891430
|View full text |Cite
|
Sign up to set email alerts
|

Mental Health, Burnout, and Job Stressors Among Healthcare Workers During the COVID-19 Pandemic in Iran: A Cross-Sectional Survey

Abstract: IntroductionThe COVID-19 pandemic has caused increasing levels of mental health problems such as anxiety and depression among doctors, nurses and other healthcare workers in hospitals or health centers. The main objective of this study was to assess the mental health, job stressors, and burnout among healthcare workers in Iran.Materials and MethodsA cross-sectional study was performed in the primary healthcare centers and hospitals affiliated with six of the medical universities in Iran. The selection of parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 62 publications
(74 reference statements)
0
11
0
Order By: Relevance
“…Similar to the results from the study by Yasmin et al (33), the present study concluded that the incidence of PTSD was higher among medical personnel with children. Numerous studies have reported increased mental health risks associated with the presence of children in the family during COVID-19 (34)(35)(36), and concerns about children's health potentially contribute to higher rates of PTSD among medical staff in families with children because children have relatively less immunity than adults.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to the results from the study by Yasmin et al (33), the present study concluded that the incidence of PTSD was higher among medical personnel with children. Numerous studies have reported increased mental health risks associated with the presence of children in the family during COVID-19 (34)(35)(36), and concerns about children's health potentially contribute to higher rates of PTSD among medical staff in families with children because children have relatively less immunity than adults.…”
Section: Discussionmentioning
confidence: 99%
“…The hazards associated with COVID-19 make people less focused on tasks linked to work, dramatically lowering their overall job performance [ 31 ]. Moreover, the COVID-19 epidemic disrupts regular operations and may increase people’s workloads and burdens at work, which lowers job performance [ 32 ]. Therefore, the following hypotheses were constructed:…”
Section: Theoretical Background and Hypothesis Developmentmentioning
confidence: 99%
“…Our study showed that the negative impact of the pandemic on mental well-being QoL may be explained by increased work stress (fear, workload, pressure, exhaustion), which may cause psychological sequelae (anxiety, depression, depersonalisation, posttraumatic stress syndrome or disorder) and sleep difficulties [ 24 35 ]. Poor mental well-being and a high level of exhaustion could even lead to burnout or job leaving intentions [ 27 , 34 , 36 40 ]. There are also studies showing that their poor mental well-being even before the pandemic strongly co-influenced other domains of QoL, and this could even have been exacerbated by the pandemic situation [ 14 , 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…There are also studies showing that their poor mental well-being even before the pandemic strongly co-influenced other domains of QoL, and this could even have been exacerbated by the pandemic situation [ 14 , 37 , 38 ]. The underlying mechanism may regard family imbalance due to the increased need to care and worry about children or for the elderly, family worries regarding the own health condition, home-schooling, social isolation, stigmatisation and limited leisure activities outside [ 13 , 24 , 28 , 40 , 41 ], thus affecting family life. Similarly, difficulties with food supplies, shopping, cooking and maintaining physical distance [ 28 , 41 ] may have decrease housekeeping QoL as well.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation